Airport pavement performance evaluation of pavement fog seal based on optimized test technology - Li, Ping; Peng, Wenju; Mao, Jing; Yan, Xin; Liu, Zhaohui; Kong, Lingyi (Frontiers in Materials, 2023)
Fog seal technology is widely used in airport asphalt pavement. The research on the performance and application of fog seal material is basically at the level of modified emulsified asphalt. The fog seal test method in the existing specification has defects. Three kinds of fog seal materials with different substrates were selected in this paper. Based on the characteristics of fog seal treatment and the relevant specifications of fog seal and airport pavement. Wet Track Abrasion Test (WTAT), Cantabro test, Water seepage test, and Pendulum instrument tester pavement friction coefficient test were improved. Test the pavement performance of different types of fog seals. The results show that the mass loss of material Cwas less than 10 % after 200 and 400 cycles of wear. The improvement effect of material C on raveling resistance and impermeability was far better than that of materials A and B. The improvement of material C on the raveling resistance of the mixture could reach 50%. The immediate improvement effect on the impermeability was nearly 100%. The skid resistance performance of the three fog seal materials decreased after treatment. The decrease in material C was more significant than in materials A and B. In constructing material C, the dose of emery should be appropriately increased. It was advisable to not be less than 0.35 kg/m 2 . The fog seal layer improves pavement performance. It has reference significance for using fog seal technology to treat early airport pavement diseases.